Insights intended to improve adaptation planning and reduce vulnerability at the local scale - Cáceres, Renato; Wandel, Johanna; Pittman, Jeremy; Deadman, Peter (Frontiers in Climate, 2024)
We live in a world of constant change, where multiple factors that generate vulnerability coincide, such as pandemics, climate change, and globalization, among other political and societal concerns.This demands the development of approaches capable of dealing with diverse sources of vulnerability and strategies that enable us to plan for and mitigate harm in the face of uncertainty.Our paper shows that the interpretation and conception that one gives to vulnerability in climate change can influence how decision-making solutions and adaptation measures are proposed and adopted. In this context, our approach integrates contextual vulnerability and decision-making planning tools to bolster the capacity to adapt at a local scale. We link our analysis to the evolution of vulnerability in climate change studies and some core articles and decisions on climate change adaptation and capacity building under the United Nations Framework Convention on Climate Change (UNFCCC) and the Conference of Parties throughout this study.